HAKEKAT HUKUM UNTUK MEWUJUDKAN ASPEK HUKUM YANG BERKEADILAN - Farahwati, Farahwati (Universitas 17 Agustus 1945 Samarinda, 2019)
Legal protection is an activity to maintain or maintain relationships in thecommunity in order to achieve justice. An upright law is guaranteeingjustice without justice can be said to be not law, therefore rely on the ruleof law in order to bring about justice for all people.Legal norms are the most dominant rules that are enforced with powerand for their violations subject to certain sanctions established by thestate.The existence of various fields of legal system in society gives rise tocertain legal systems which are also the structure and process of the law.The legal system covers various legal subsystems which then greatlyinfluences the ongoing process of various fields of law.The nature of the law covers the entire legal system wcihc is an activity toimplement and apply justice and take legal action against any violationsor deviations of law committed by legal subjects either through judicialprocedures or through non judicial procedures.